Microwave Signal Spatial Domain Transformation using Signal Processing and Image Reconstruction Method - Chew, Kim Mey; Rubita, Sudirman; How, Yu Hang; Yong, Ching Yee (2014)
This study focused on the transformation of frequency domain signals from a planar scanning into a planar image. Computer Simulation Technology Microwave Studio is an efficient tool for 3D Electromagnetic simulation. It performed high accuracy simulation for 3D model simulation. This electromagnetic simulator is used to simulate a round phantom which has a created target inside the phantom. An antenna emitted microwave signal is being placed in front of the phantom to transmit a short pulse to the model. Scanning was performed along the fixed axis in front of the model. A mono-static antenna was used as the transmitter and receiver of the signals. The frequency domain data sets reflected and received by the antenna were imported into MATLAB software for image reconstruction. Subtraction method was used to reduce the reflection of antenna which was recognized as the unwanted noise in the signals. All time domain signals were smoothed to reduce the sharp peak and had a more continuous waveform, and arranged into matrix form. Image reconstruction function in MATLAB was used to transform the matrix envelope into a planar image. The phantom and target is identified by the different intensity of the colormap showed in the reconstructed image.